2020
DOI: 10.1002/ped4.12180
|View full text |Cite
|
Sign up to set email alerts
|

Self‐knotting of distal end of nasogastric tube—Not an uncommon possibility

Abstract: Importance A nasogastric tube is used commonly to decompress the stomach and provide enteral feeding in surgical and medical practice. Sometimes this safe and innocent‐looking tube may lead to unexpected complications. We focus here on the possibility of spontaneous ‘lariat loop’ knotting of the nasogastric tube when some resistance is felt on tube retrieval and describe a method of safe tube removal. Case presentation We present a case of self‐knotting of a nasogastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The occurrence of knotting can be mitigated by employing established procedures and maneuvers designed to facilitate smooth insertion. These include ensuring adequate lubrication, selecting an appropriate tube size, ensuring proper insertion length, utilizing a wide-bore tube, cooling the tube, enhancing rigidity by inserting a Fogarty catheter through a suction port, displacing the larynx forward, applying lateral neck pressure, providing direct guidance with two fingers in the mouth, and employing Magill forceps under direct laryngoscopic visualization [ 11 ]. Determining the proper tube length involves measuring the distance from the nose to the pinna and from the pinna to the xiphoid process, then adding 5cm for accurate placement.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of knotting can be mitigated by employing established procedures and maneuvers designed to facilitate smooth insertion. These include ensuring adequate lubrication, selecting an appropriate tube size, ensuring proper insertion length, utilizing a wide-bore tube, cooling the tube, enhancing rigidity by inserting a Fogarty catheter through a suction port, displacing the larynx forward, applying lateral neck pressure, providing direct guidance with two fingers in the mouth, and employing Magill forceps under direct laryngoscopic visualization [ 11 ]. Determining the proper tube length involves measuring the distance from the nose to the pinna and from the pinna to the xiphoid process, then adding 5cm for accurate placement.…”
Section: Discussionmentioning
confidence: 99%
“…Blockage of the nasogastric tube is an easily underestimated complication and is particularly common when thicker enteral feeds, bulking agents and medications are delivered through relatively small nasogastric tubes [9]. Many case reports have shown that excessively long cannulae tend to lead to nasogastric tube kinking [10][11][12]. Prevention is a key factor in the treatment of nasogastric tube blockage.…”
Section: Discussionmentioning
confidence: 99%